Constitutional preambles : a comparative analysis - Voermans, W. J. M., 1961- (Elgar monographs in constitutional and administrative law, 2017)
While their use and significance have increased in recent decades, constitutional preambles have received only scant attention in academic literature. This presents a uniquely quantitative and qualitative analysis of all the preambles currently in force around the world and addresses fascinating questions concerning their occurrence, content, style, function and legal status. Studying preambles not only helps us understand the phenomenon itself, but also teaches us more about constitutions and the constitutional systems in which they are situated. Constitutional Preambles illuminates the great variety that constitutional preambles display. The authors discuss the different styles, legal and non-legal functions, and content of the preambles, as well as their use in the courts. This work also contains a carefully curated anthology of the world's preambles in English.